Phytosteroids beyond estrogens: Regulators of reproductive and endocrine function in natural products. (15th February 2017) - Dean, Matthew; Murphy, Brian T.; Burdette, Joanna E.
Abstract: Foods and botanical supplements can interfere with the endocrine system through the presence of phytosteroids – chemicals that interact with steroids receptors. Phytoestrogens are well studied, but compounds such as kaempferol, apigenin, genistein, ginsenoside Rf, and glycyrrhetinic acid have been shown to interact with non-estrogen nuclear receptors. These compounds can have agonist, antagonist, or mixed agonist/antagonist activity depending on compound, receptor, cell line or tissue, and concentration. Some phytosteroids have also been shown to inhibit steroid metabolizing enzymes, resulting in biological effects through altered endogenous steroid concentrations. An interesting example, compound A (4-[1-chloro-2-(methylamino)ethyl]phenyl acetate hydrochloride (1:1)) is a promising selective glucocorticoid receptor modulator (SGRM) based on a phytosteroid isolated from Salsola tuberculatiformis Botschantzev . Given that 6.9 billion of herbal supplements are sold each year, is clear that further identification and characterization of phytosteroids is needed to ensure the safe and effective use of botanical supplements. Highlights: Botanicals contain phytosteroids that bind non-estrogen steroid receptors. Kaempferol, apigenin, and genistein bind progesterone and androgen receptors. Ginsenoside Rf and glycyrrhetinic acid interact with corticoid receptors. Compound A is a novel selective glucocorticoid, based on a phytosteroid. Characterization of phytosteroids will help elucidate their safe and effective use.